2000
DOI: 10.1001/archfami.9.4.359
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Physicians' Prevention-Related Practices: Findings From the Women Physicians' Health Study

Abstract: Being a primary care practitioner and having related healthy habits oneself were the most significant correlates of US women physicians' self-reported prevention-related counseling and screening practices. These findings suggest potential new directions for physician training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
158
2
17

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(183 citation statements)
references
References 30 publications
6
158
2
17
Order By: Relevance
“…Other studies have demonstrated that physicians' personal behavior influences practice behavior, with respect to exercise 24,25 and preventive care 26 . We found that personal experience with the test was also an important factor related to test ordering for patients, perhaps as a result of increased physicians' familiarity with the test and comfort in ordering it for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that physicians' personal behavior influences practice behavior, with respect to exercise 24,25 and preventive care 26 . We found that personal experience with the test was also an important factor related to test ordering for patients, perhaps as a result of increased physicians' familiarity with the test and comfort in ordering it for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Primary care physicians (PCPs) are more likely to practice prevention-related counseling than specialists. 18 Thus patients who have a primary care physician as their usual source of care are more likely to receive counseling regarding weight loss and maintaining a healthy weight, and to attempt weight loss. In landmark studies by Shi et al 19 and Starfield et al, 20 US states with more primary care physicians had lower mortality rates and higher birth weights.…”
mentioning
confidence: 99%
“…Physician example and advice can pivotally impact upon lifestyle-related cancer risk factors (LRCRF), especially smoking, among their patients and the general population 3) . This may be particularly important for female physicians who provide standards for other women 4,5) . Unfortunately, in much of the world, the LRCRF are very prevalent in the general population and among physicians, especially women.…”
mentioning
confidence: 99%